2019
DOI: 10.31234/osf.io/n8pv3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychometric properties of the Neuropsychiatric Inventory: a review

Abstract: Neuropsychiatric symptoms (NPSs) cause a significant burden to individuals with memory disorders and their families. Insights into the clinical associations, neurobiology, and treatment of NPSs are largely dependent on informant questionnaires, such as the commonly used Neuropsychiatric Inventory (NPI). Like any scale, the utility of the NPI relies on its psychometric properties, but unlike many scales, the NPI faces unique challenges related to its skip-question and scoring formats.We examined and reviewed th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A Western measure may not be as sensitive when being applied in other cultures 52 . Recent reviews revealed that some cultural adaptions of the NPI may ascertain cultural sensitivity more than the others and there appears to be lacking investigation of some aspects of validity of the measure across cultures 53,54 . The presence of BPSD is multifactorial, resulting from the interacting effects of people with dementia, carers, and environmental factors 55 .…”
Section: Discussionmentioning
confidence: 99%
“…A Western measure may not be as sensitive when being applied in other cultures 52 . Recent reviews revealed that some cultural adaptions of the NPI may ascertain cultural sensitivity more than the others and there appears to be lacking investigation of some aspects of validity of the measure across cultures 53,54 . The presence of BPSD is multifactorial, resulting from the interacting effects of people with dementia, carers, and environmental factors 55 .…”
Section: Discussionmentioning
confidence: 99%
“…by multiplying the severity score of 0 to 3 by the frequency score of 0 to 4 so that the values 5, 7, 10 and 11 cannot be observed. 49, 50 Using symptom-specific instruments such as the Apathy Evaluation Scale (score range 18– 71), Cohen-Mansfield Agitation Inventory (score range 29–203), and Geriatric Depression Scale (score range 0–30) may not only help to fully characterize specific NPS, but also enables the use of statisical modelling due to a larger variation in potential scores compared to the NPI.…”
Section: Discussionmentioning
confidence: 99%
“…Since similar symptoms can be observed after a head injury, the NPI has also been used recently for patients with TBI ( 25 ). The NPI has good test-retest and inter-rater reliability ( 26 ), and the validity of each item has proven reasonably high ( 27 ).…”
Section: Methodsmentioning
confidence: 99%